Analisis Pemikiran Harun Nasution: Kekuasaan, Kehendak Mutlak Tuhan dan Kebebasan Manusia - Pratama, Finsa Adhi; Sumantri, Sumantri (Aqlania, 2022)
This study aims to examine the thoughts brought by Harun Nasution regarding power, God's absolute will and human freedom in an analysis of thought. This is based on Harun Nasution's thoughts which are often the subject of long discussions among thinkers and scholars, one of which is the statement that abandoning rational thought has an impact on the backwardness of Muslims and reason symbolizes human power. His thoughts received various responses from thinkers and scholars, so researchers were interested in examining his thoughts. The author uses qualitative research methods of literature and interpretive analysis, the author tries to collect data then filter and cite various data sources which are then interpreted in order to obtain a valid conclusion. The author's validation method uses method, time and theory triangulation. The results show that Harun Nasution views that God's power and will are limited by rational thinking. God has given freedom to humans according to His Sunnah. God gives freedom to humans to determine what they want so that this human freedom seems to limit the power and will of God. Every moment humans have to choose from several life choices which are essentially still within the scope of God's will.